Terror Per Capita - Michael Jetter; David Stadelmann (Center for Economic Studies and ifo Institute (CESifo), 2017)
Usually, studies analyzing terrorism focus on the total number of casualties or attacks in a given county. However, per capita rates of terrorism are more likely to matter for individual welfare. Analyzing 214 countries from 1970 - 2014, we show that three stylized findings are overturned in terms of sign, magnitude, and statistical significance when investigating terror per capita. Democracy, previously associated with more casualties, emerges as a marginally negative predictor of terror per capita. A larger share of Muslims in society is, if anything, associated with less terrorism. Similar conclusions apply to language fractionalization.
Keywords: D74; O57; Z12; 330; terrorism; terror per capita; democracy; Islam; language fractionalization